Peran Gerakan Literasi Dan Minat Baca Dalam Membentuk Karakter Religius Siswa MTsN 5 Jombang - Anik Zuroidah; Muhtadi; Abdul Rouf (FAI- Undar, 2019)
Literacy becomes the hot topic spoken among practitioners especially in education environment. However, many people do not know what activities are included in it. An online information mentions that literacy is intended to carry out the habit of thinking followed by the process of reading and writing, which in turn can create a work. In Islam, the basis of this literacy activity is very strong. This can be seen in the Qur'an surah Al Alaq verse 1, which means: